El material reciclable y su incidencia en el desarrollo de la inteligencia lógico matemático en los niños y niñas de 4 años de la Unidad Educativa”Belisario Quevedo” parroquia Pujilí, cantón Pujilí de la provincia de Cotopaxi en el año lectivo 2013-2014 - Nieto Guamangallo, Alexandra Elizabeth (2015)
The purpose of this study was to determine an adequate teaching – learning process with regard to the logical-mathematical intelligence. The research consists of a workshop which includes recreational activities such as: „Los niños de los bolos, Ratones a su casita, Vamos a pescar‟ among others. Therefore, this research study carried out at „Belisario Quevedo‟ Elementary School will allow developing the best children‟s skills according to their ages. One of the goals into this research is to help the educational work, since with early ages is very difficult to draw the child‟s attention, especially when they are reasoning processes. A practical, fun, and valid manner of doing it, it is through recreational activities. A child learns by manipulating and exploring his or her world. Through these activities, which are purely games, the child develops his or her cognitive potential.